Hybrid pyrimidine alkynyls inhibit the clinically resistance related Bcr-AblT315I mutant. Issue 17 (1st September 2015) - Lu, Xiaoyun; Zhang, Zhang; Ren, Xiaomei; Pan, Xiaofeng; Wang, Deping; Zhuang, Xiaoxi; Luo, Jingfeng; Yu, Rongmin; Ding, Ke
Graphical abstract A series of pyrimidine alkynyl derivatives were designed and synthesized as new Bcr-Abl inhibitors by hybriding the structural moieties from GNF-7, ponatinib and nilotinib. Compound 4e is one of the most potent compounds.